Hubungan Minat Belajar Mahasiswa Tata Rias dan Kecantikan terhadap Hasil Belajar pada Mata Kuliah Perawatan Wajah Teknologi - Chan, Putri Afsyari; Yasmin, Nadya; Dewi, Siska Miga (ANWARUL, 2025)
This study aims to analyze the relationship between learning interest of Cosmetology and Beauty students and learning outcomes in the Facial Care Technology course. Learning interest is understood as an attraction that motivates students to actively participate in learning, while learning outcomes reflect the level of understanding and skills acquired. The research method used is descriptive quantitative with a correlational approach. Data were collected through a closed questionnaire using a Likert scale to evaluate five aspects: social, academic, emotional, personal, and environmental. The sample in this study consisted of 100 samples consisting of make-up and beauty students from the 2021 intake who had met certain criteria, selected using a purposive sampling technique. The results showed that there is a significant relationship between learning interest and learning outcomes. Students' learning interest contributes to their academic achievement, especially in the indicators of concept understanding, practical skills, and application in real situations. With a positive correlation coefficient, it is concluded that an increase in learning interest is directly proportional to an increase in learning outcomes. This research also provides important implications for the management of education in the field of Cosmetology and Beauty, especially in designing learning strategies that support the development of student learning interests. This study suggests improving academic support and learning facilities to encourage interest and optimal learning outcomes. The findings contribute to the development of theory and practice in the field of cosmetology education, with the hope of improving the quality of competitive graduates.